UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI EKONOMI KREATIF MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING KELAS IX SMP NEGERI 1 PASARIBU TOBING - Hotnida Masdiana Gorat (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2024)
This research aims to investigate methods to enhance the learning outcomes of creative economic subjects among 9th-grade students at SMP Negeri 1 Pasaribu Tobing through the implementation of a problem-based learning model. The research findings indicate an improvement in student engagement throughout the stages of the Problem-Based Learning model in the subject of Social Sciences (Creative Economics), with nearly all types of activities exceeding 70% from Cycle I to Cycle II. Student learning outcomes showed improvement with the utilization of problem-based learning models. The increase in learning outcomes is evident from the rise in the number of participants achieving the Minimum Completion Criteria (KKM), which increased by 24.14%. The average learning outcomes score was 69.66 in Cycle I, which increased to 80.69 in Cycle II. Furthermore, students' responses and attitudes towards the implemented problem-based learning model were highly positive.